Divine Providence and the Dog in the Book of Tobit - Macatangay, Francis M. (Journal of theological interpretation, 2019)
The presence of the dog is a puzzling narrative detail in the Book of Tobit. This study examines the canine presence in the story in light of divine providence and argues that the presence of the dog playing its assigned function in the story can point to the unseen reality that the divine creative order, which is the harbinger and bearer of divine providence, continues to hold albeit in hidden ways. Like the disguised Raphael, who personifies divine providence in the narrative, the inclusion of the dog in the story can be viewed as a concealed indication of the enduring aliveness of God's life-giving and providential intentions for his people.